Insulin Resistance, Obesity, Hypertension, and Renal Sodium Transport - Shoko Horita; George Seki; Hideomi Yamada; Masashi Suzuki; Kazuhiko Koike; Toshiro Fujita (International Journal of Hypertension)
Sodium transport through various nephron segments is quite important in regulating sodium reabsorption and blood pressure. Among several regulators of this process, insulin acts on almost all the nephron segments and is a strong enhancer of sodium reabsorption. Sodium-proton exchanger type 3 (NHE3) is a main regulator of sodium reabsorption in the luminal side of proximal tubule. In the basolateral side of the proximal tubule, sodium-bicarbonate cotransporter (NBCe1) mediates sodium and bicarbonate exit from tubular cells. In the distal nephron and the connecting tubule, epithelial sodium channel (ENaC) is of great importance to sodium reabsorption. NHE3, NBCe1, and ENaC are all regulated by insulin. Recently with-no-lysine (WNK) kinases, responsible for familial hypertension, stimulating sodium reabsorption in the distal nephron, have been found to be also regulated by insulin. We will discuss the regulation of renal sodium transport by insulin and its roles in the pathogenesis of hypertension in insulin resistance.